The Principles and Experience of Existentialist Pedagogy - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1997)
In this article the author presents the conception of existentialist pedagogy and its basic principles. She introduces the representatives of existentialism and analyses the experience of the Summerhill existentialist school: its purpose, tasks, the standpoint for a child, and the content and organization of education.